2017
DOI: 10.1111/jam.13478
|View full text |Cite
|
Sign up to set email alerts
|

Extract of Syzygium aromaticum suppress eEF1A protein expression and fungal growth

Abstract: This study is based on a detailed study of antifungal action exerted by clove extract, and proposed that down-regulation of eEF1A protein expression may contribute to its antifungal activity. These results may have clinical significance for future application of clove extract as a natural antifungal agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
(88 reference statements)
1
4
0
Order By: Relevance
“…The results revealed that the crude extract contained 18 different chemical compounds with different concentrations such like eugenol, trans-caryophyllene, humulene, anthracenedione, cedran-diol, citroflex A and lucenin 2. This result is consistent with that of Wagn et al (2017) who found that the major compounds in clove alcoholic extract analysis by GC/MS were eugenol, acetyl eugenol , caryophyllene , and humulene followed by a-farnesene and caryophylleneoxide. These notable differences in composition may be due to extraction methods as well as genetic diversity and agronomic treatments (Mahanta et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…The results revealed that the crude extract contained 18 different chemical compounds with different concentrations such like eugenol, trans-caryophyllene, humulene, anthracenedione, cedran-diol, citroflex A and lucenin 2. This result is consistent with that of Wagn et al (2017) who found that the major compounds in clove alcoholic extract analysis by GC/MS were eugenol, acetyl eugenol , caryophyllene , and humulene followed by a-farnesene and caryophylleneoxide. These notable differences in composition may be due to extraction methods as well as genetic diversity and agronomic treatments (Mahanta et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we found the expression of phosphopyruvate hydratase activity-related protein CB033636 (spot 31) was increased in SP4, CP2 and CP4 samples, but decreased in the SP2 sample. The phosphopyruvate hydratase was reported to be involved in the defense against fungi [ 70 , 71 ]. Previous studies have shown that a molecule associated with powdery mildew resistance, NORTIA (NTA), plays a role in the process of reception pollen tubes in synergids, suggesting that this protein is involved in both pollen tube acceptance and powdery mildew infections [ 72 ] and the decrease in SP2 may contribute to pollination response at early stage.…”
Section: Resultsmentioning
confidence: 99%
“…CEO interferes with the expression of virulence-related genes involved in the flagellum, PEB1, PEB4, LPS and serine protease, with significant antibacterial and potentially virulence-modulating effects on Campylobacter jejuni (81). eEF1A protein interacted with several viral proteins, leading to enhanced viral replication, reduced apoptosis and increased cellular transformation; therefore, Wang et al (82) suggested that downregulation of eEF1A protein expression may be another important mechanism for exerting its antifungal activity.…”
Section: Antibacterial Activitymentioning
confidence: 99%